The power of constructive criticism and its effect on students' learning motivation - Wulandari, Anggi Putri Suri; Anugerahwati, Mirjam (Universitas Muhammadiyah Sidoarjo, 2021)
The present study sought to understand EFL students’ perception on the use of oral constructive criticism given by faculty members in the classroom and whether it has any effect on the students’ motivation in learning English. The participants of the study were 86 EFL students from 5 outstanding universities in Malang, East Java, Indonesia. The data were collected through a questionnaire and an interview. The results of the study revealed that the 86 EFL students had positive perceptions on the use of oral constructive criticism. The students were helped in some ways in learning English by means of receiving oral constructive criticism from their faculty members. The students considered oral constructive criticism a confirmation whether they did the right things in the learning process. More prominently, the result showed that the use of oral constructive criticism played a big role in boosting the students’ motivation in learning English. The students did not feel constructive criticism as a thread that inhibited them from being their best version of themselves in learning English. Instead, the students were strongly motivated to study hard and get good scores because of oral constructive criticism that they received during the teaching and learning process. HIGHLIGHTS : Constructive criticism is considered a necessary tool to help students recognize their mistake, learn from it, and stop repeating the same mistake in the near future. Faculty members should continuously provide constructive criticism for students to boost their motivation in learning English. Students feel highly motivated to study hard and achieve high grades because of the verbal constructive criticism they receive during the teaching and learning process.